Estudo retrospectivo imunoistoquímico e pesquisa por PCR em fezes e sorologia para Lawsonia Intracellularis em equinos no Estado de Minas Gerais - Brasil - Cristiane Viana Guimaraes (2008)
The proliferative enteropathy caused by intracellular bacteria, Lawsonia intracellularis, has been described in equine in Australia, United States, Canada and in countries of Europe, (Switzerland and Belgium). Currently, the disease has not been diagnosed in any country of Latin America. The predominance of the disease in equine is still unknown. A retrospective study was conducted using paraffin blocks of equine cases from the veterinarian schools of Universidade Federal de Minas Gerais (UFMG) and Universidade Federal de Lavras (UFLA). Also a prospective study using serology and PCR for detecting antibodies and L. intracellularis shedding in fecal samples was conducted in different equine herds in the state of Minas Gerais, Brasil. Fifty-one cases of equines with enteric disorders from the period of 1970 to 2006 from UFMG and nine cases of UFLA were compiled and selected from the period of 2000 to 2007. Histological cuts of the blocks containing fragments of intestine and stomach were prepared in signalized glass-slides, and were submitted to IHQ using the method of Streptavidin, polyclonal antibody against L. intracellularis and ACE (Amino Etil-carbazol) cromogen solution. No positive sample in IHQ was identified. For the longitudinal study, sera and fecal samples from 223 animals from 14 horse farms and veterinarian schools of UFMG a serological test using the imunoperoxidase technique in glass sheets and PCR were used. From the 223 samples serologically tested, eight equine had 1:60 titer, and were considered positive. The PCR technique in feces for bacterias DNA detection identified seven positive equine for L. intracellularis. Seropositivity and detection of bacteria in colts feces in equine population in the State of Minas Gerais, Brasil, indicates the presence of the agent and the possibility of the disease associated with the infection. This should be an alert to clinics as possible differential diagnosis of enteric disease equine